Development of Three-Language Storybooks as a Medium for Children's Language Learning - Hesti Wela Arika; Na'imah Na'imah; Rosmiati Rosmiati; Yuhasriati Yuhasriati (AL-ISHLAH: Jurnal Pendidikan, 2023)
Language in early childhood is very important to be stimulated early. So early childhood language learning must be innovative because the language will continue to develop. This study aims to design and develop trilingual storybook media as an alternative to children's language learning media that can stimulate children's language with foreign languages, namely Indonesian, English and Arabic. This research uses a development research method, namely RD (Research and Development) developed by Dick and Carry, namely the ADDIE model. The subject of the study was Raudhatul Athfal in Yogyakarta. The object of research is the feasibility of a trilingual storybook media for children's language learning which will be seen in terms of validity and effectiveness in learning in schools. Data collection techniques use questionnaires. Data analysis using quantified data. Based on the results of the analysis of material validation, media and effectiveness and obtained the following values: validation of Indonesian material (85%), validation of English material (95%), validation of Arabic material (85%), media validation (82%) and effectiveness value (90%). The evaluated quality of the created and validated media indicates that it should be used to teach children's language. This book offers new approaches to education, such as creating a storybook in three languages to help kids learn more about the world around them. The next linguist will be able to compile a collection of tales in some of those other languages.